2022
DOI: 10.1038/s41598-022-22802-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of the reprogramming factor NeuroD1 is critical for neuronal conversion efficiency from different cell types

Abstract: Several transcription factors, including NeuroD1, have been shown to act as neuronal reprogramming factors (RFs) that induce neuronal conversion from somatic cells. However, it remains unexplored whether expression levels of RFs in the original cells affect reprogramming efficiency. Here, we show that the neuronal reprogramming efficiency from two distinct glial cell types, microglia and astrocytes, is substantially dependent on the expression level of NeuroD1: low expression failed to induce neuronal reprogra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…One hypothesis for the failure of glia-to-neuron conversion is likely due to the low expression level of Neurod1. 27 , 47 , 48 Without improved gene delivery to restrict transgene expression in glial cells, however, simply increasing the expression levels of Neurod1 by using higher viral doses 48 or an enhanced GFAP promoter 41 may further increase the leakage into endogenous neurons, a strategy counterproductive to glia-to-neuron reprogramming. In fact, a new study 49 demonstrates that the failure of Neurod1-induced microglia-to-neuron conversion is not due to the low expression level as comparable or even higher expression levels of Neurod1 cannot induce microglia-derived neurogenesis, arguing against the conclusion from the original study.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis for the failure of glia-to-neuron conversion is likely due to the low expression level of Neurod1. 27 , 47 , 48 Without improved gene delivery to restrict transgene expression in glial cells, however, simply increasing the expression levels of Neurod1 by using higher viral doses 48 or an enhanced GFAP promoter 41 may further increase the leakage into endogenous neurons, a strategy counterproductive to glia-to-neuron reprogramming. In fact, a new study 49 demonstrates that the failure of Neurod1-induced microglia-to-neuron conversion is not due to the low expression level as comparable or even higher expression levels of Neurod1 cannot induce microglia-derived neurogenesis, arguing against the conclusion from the original study.…”
Section: Discussionmentioning
confidence: 99%
“…Forskolin activates adenylate cyclase to produce cyclic adenosine monophosphate (cAMP), and this cAMP activates protein kinase A, which improves the survivability and maturation after neuronal conversion (Liu et al, 2013). Forskolin is also known to induce Brn2 expression (Liu et al, 2021), which has been shown to promote NeuroD1-mediated neuronal reprogramming (Matsuda-Ito et al, 2022). These facts suggest that VPA and Forskolin enhance neuronal conversion, possibly through the induction of endogenous gene expression associated with reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared primary microglia from mouse using a previously reported protocol (Matsuda et al, 2019; Matsuda‐Ito et al, 2022). We dissected cortexes of BL6 mice at postnatal day 1 (P1) or Hexb‐Cre ERT2 ::Stop‐YFP mice at P4 (Masuda et al, 2020) after peeling of meninges to obtain microglia from glial cell mixtures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations